Comparing discourse to officer perceptions: the problems of war and militarization in wildlife crime enforcement - Runhovde, Siv Rebekka (Critical criminology, 2017)
‘War’ has become a common model and metaphor for biodiversity conservation in Africa. By discussing the specific challenges of wildlife crime enforcement in Uganda, this article challenges the ‘war on wildlife crime’ discourse. It concludes that in the context of Uganda, the discourse is profoundly unhelpful because of a lack of alignment between the problems highlighted by Ugandan law enforcement officers interviewed and the solutions typically favoured in the ‘wars on crime’. Most wildlife crimes are subsistence-driven and interviewees’ requests are for basic equipment and conventional capacity building. Findings demonstrate that the language of war, militarization and securitization should be used with caution as it risks constructing an image of wildlife crime that is misleading - and one that prevents responses that are effective in the long term.